Relationship between happiness and different levels of physical activity - Mohammadi, Eftekhar; Batvandi, Ziba; Saberi, Amin (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Happiness is an important factor in human life. Aim of Study. The aim of this research was to examine the relationship between happiness and different levels of physical activity of students of the Khorramshahr Marine Science and Technology University in Iran. Materials and Methods. The following tests were used in the statistical analysis: t-test, one-way ANOVA and Tukey’s range test. The study sample comprised 156 students (53 men, 103 women) selected by way of cluster sampling from the population of all 1,200 students of the Khorramshahr Marine Science and Technology University in the academic year of 2013-2014. The participants completed a demographic questionnaire, physical activity questionnaire, and Oxford Happiness Questionnaire (OHQ) during one session. Results. The t-test results revealed non-significant differences in the happiness levels between the male and female students (p < 0.05). The results of ANOVA and Tukey’s range test showed significant differences in happiness levels between physically active and semi-active students (p < 0.01), and between physically active and non-active students (p < 0.01). Conclusions. Physical activity is an effective determinant of the level of happiness
Keywords: happiness; students; physical activity